Refractory scleroderma renal crisis precipitated after high-dose oral corticosteroids and concurrent intravitreal injection of bevacizumab. (August 2020) - Hanna, Ramy M; Abdelnour, Lama; Zuckerman, Jonathan E; Ferrey, Antoney J; Pai, Alex; Vahabzadeh, Kambiz; Wilson, James; Torres, Everado A; Kalantar-Zadeh, Kamyar; Kurtz, Ira B
Scleroderma renal crisis is a serious complication that can develop in certain patients with systemic sclerosis. Some risks have been identified as potential triggers of scleroderma renal crisis, including the high-dose oral corticosteroids. Here, we present a patient who developed clinically severe systemic sclerosis and scleroderma renal crisis after exposure to oral corticosteroids and intravitreal vascular endothelial growth factor blockade with bevacizumab for cotton wool spots. The patient's scleroderma renal crisis was severe, progressive, and refractory to the standard of care therapy: oral captopril. Biopsy showed a diffuse thrombotic microangiopathy and findings consistent with scleroderma renal crisis. We hypothesize that depletion of systemic vascular endothelial growth factor with intravitreal anti–vascular endothelial growth factor injections likely contributed to the particularly severe presentation seen in this case. Though the finding of a monoclonal gammopathy of undetermined significance is another complicating factor, this case suggests that vascular endothelial growth factor inhibition may be a newly recognized trigger of scleroderma renal crisis.